Ekspresi P16INK4a pada Squamous Cell Carcinoma Serviks Uteri dan Cervical Intraepithelial Neoplasia 1, 2, 3 - Luh Yeni Laksmini; Moestikaningsih .; Gede Raka Widiana; Ni Putu Sriwidyani; Ketut Mulyadi (Majalah Patologi Indonesia, 2014)
Background Cervical cancer is the second most common cancer in female in the world. In Bali, in 2008, cervical cancer is the second most common malignancy after breast cancer. This cancer has known to develop from precancerous lesions, cervical intraepithelial neoplasia (CIN).There is difficulty to determine grade of dysplasia of the uterine cervix and to predict wheather the lesion has potency of progression. The expression of P16INK4a has correlation with degree of cervical dysplasia and carcinoma. The aim of this study is to evaluate expression of P16INK4a in squamous cell carcinoma (SCC) of cervix uteri and CIN1, CIN2, CIN3. Methods A cross sectional analytic study was performed on 60 samples that divided into 10 CIN1, 10 CIN2, 10 CIN3, and 30 SCC. Samples were tooken from block paraffin archive from Private Laboratory in Denpasar and Anatomical Pathology Laboratory Sanglah Hospital, during January 1st 2011 until Juny 30th 2013. Immunostaining was performed to determine the expression score of P16INK4a. Expression of P16INK4a was determined by for scoring system base on staining grade and intensity. The result was analyzed by Kruskal Wallis test with level of significance ÃŽÂ± at p